-3k-2(5k-6)=90

Simple and best practice solution for -3k-2(5k-6)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3k-2(5k-6)=90 equation:


Simplifying
-3k + -2(5k + -6) = 90

Reorder the terms:
-3k + -2(-6 + 5k) = 90
-3k + (-6 * -2 + 5k * -2) = 90
-3k + (12 + -10k) = 90

Reorder the terms:
12 + -3k + -10k = 90

Combine like terms: -3k + -10k = -13k
12 + -13k = 90

Solving
12 + -13k = 90

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -13k = 90 + -12

Combine like terms: 12 + -12 = 0
0 + -13k = 90 + -12
-13k = 90 + -12

Combine like terms: 90 + -12 = 78
-13k = 78

Divide each side by '-13'.
k = -6

Simplifying
k = -6

See similar equations:

| 2xsquared+6x=360 | | 1/7+7/12= | | 28b=2 | | 235.6/100 | | 4+4b=5(-8b-8) | | 28=2 | | 9c+10.6=12c-9 | | 235.6/10 | | V-11/14=3/14 | | -5(-6x+2w-5)= | | 3(-7x+4)=-72 | | 3+7(7-3x)=-38-3x | | 16x+-16-2=4 | | y+12-2=130 | | 6x-12=2x+24 | | 2x-4=(x-1)+3 | | 1/2x-3=5x-5/7 | | 2x^3-x^2+40=0 | | 70+95= | | 7h-1×1/7 | | 0y-4=-4 | | 12=5x+3(2-x) | | y-27+3=-63 | | x-2y+27y=5x | | 12m-84+6m+6=50m-62 | | p/7=37 | | H=2.38(38)+61.41 | | X-19+x+75=180 | | 7(x-4)=-147 | | 5a-20=-5a+8a | | f(x)=-8x+5 | | 6u-9/3=u |

Equations solver categories